2021
DOI: 10.3390/jcm10194507
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Bilateral Simultaneous Hip and Knee Arthroplasty versus Staged Arthroplasty in a High-Volume Center Comparing Blood Loss, Peri- and Postoperative Complications, and Early Functional Outcome

Abstract: Purpose: In recent years, there has been increasing interest in the use of simultaneous hip and knee arthroplasty compared to staged procedures in patients with bilateral pathology. The aim of this study was to compare simultaneous and staged hip and knee arthroplasty in patients with bilateral pathology by assessing the transfusion rate, postoperative hemoglobin drop, length of stay (LOS), in-hospital complications, 30-day readmissions and early functional outcome. Methods: We conducted a retrospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Another recent study comparing the two tibial components observed similar clinical results using the same evaluation method [20]. In the literature, there are only a few specific clinical comparisons between the components in bilateral staged TKA [21,22]. Our study recorded comparable clinical and functional outcomes using the Knee Society Score.…”
Section: Discussionsupporting
confidence: 66%
“…Another recent study comparing the two tibial components observed similar clinical results using the same evaluation method [20]. In the literature, there are only a few specific clinical comparisons between the components in bilateral staged TKA [21,22]. Our study recorded comparable clinical and functional outcomes using the Knee Society Score.…”
Section: Discussionsupporting
confidence: 66%
“…Similar variations were observed in StaBTKA studies, from the smaller cohort of Berend [ 15 ], with 141 cases, to the extensive dataset of Tsay [ 38 ], with 45,419 cases. Sex distribution also varied, with male percentages ranging from as low as 4.10% in the study by Koh [ 39 ] to as high as 58.49% in the study by Najfeld [ 40 ].…”
Section: Reviewmentioning
confidence: 99%
“…Bilateral hip and knee arthroplasties have been extensively studied, including case series of bilateral arthroplasty, comparison of bilateral arthroplasty with unilateral arthroplasty, and direct comparisons of bilateral simultaneous and sequential THA 1-6 , TKA [6][7][8][9][10] , and UKA [11][12][13][14] . The systematic reviews and meta-analyses have summarized that bilateral simultaneous TKA results in a lower risk of deep infection and respiratory complications but increased 30-day mortality, pulmonary embolism, and blood transfusion rates compared with bilateral sequential TKA [25][26][27] .…”
Section: Bilateral Taa Literaturementioning
confidence: 99%
“…Those in support of bilateral simultaneous arthroplasty have noted significant cost savings as well as multiple reports of noninferior and even superior perioperative complication rates, patient-reported outcome measures, and early rehabilitation when compared with sequential procedures. This literature includes comparisons involving bilateral total hip arthroplasty (THA) [1][2][3][4][5][6] , total knee arthroplasty (TKA) [6][7][8][9][10] , and unilateral knee arthroplasty (UKA) [11][12][13][14] . The literature is less complete for TAA, with only a few studies demonstrating successful outcomes after bilateral TAA [15][16][17][18] .…”
mentioning
confidence: 99%